Addressing new aspects of surveillance in late mediaeval England, 1350-1550 - Chatziathanasiou, Manos (Mos Historicus: A Critical Review of European History, 2024)
The paper addresses new aspects of surveillance in late medieval England. New approaches to the study of the phenomenon are introduced, while a limited study puts some of the author’s suggestions to the test. The study addresses the modus operandi of political and labour surveillance focusing on late medieval English towns. Surveillance was intensified after the Black Death. Institutional and noninstitutional surveillance were part of everyday life, but they were also used by the ruling elites to consolidate their power. Surveillance was endured by the lower social ranks. Nevertheless, evidence suggests that sometimes popular classes resisted surveillance or even used it to their own advantage.